Superconductivity emerging from a pressurized van der Waals kagome material Pd3P2S8. (1st April 2023) - Wang, Qi; Qiu, Xiao-Le; Pei, Cuiying; Gong, Ben-Chao; Gao, Lingling; Zhao, Yi; Cao, Weizheng; Li, Changhua; Zhu, Shihao; Zhang, Mingxin; Chen, Yulin; Liu, Kai; et al.
Abstract: Kagome materials have been reported to possess abundant and peculiar physical properties, which provide an excellent platform to explore exotic quantum states. We present a discovery of superconductivity in van der Waals material Pd3 P2 S8 composed of Pd kagome lattice under pressure. Pd3 P2 S8 displays superconductivity for those pressures where the semiconducting-like temperature dependence of the resistivity turns into a metallic one. Moreover, it is found that the increased pressure results in a gradual enhancement of superconducting transition temperature, which finally reaches 6.83 K at 79.5 GPa. Combining high-pressure x-ray diffraction, Raman spectroscopy and theoretical calculations, our results demonstrate that the observed superconductivity induced by high pressure in Pd3 P2 S8 is closely related to the formation of amorphous phase, which results from the structural instability due to the enhanced coupling between interlayer Pd and S atoms upon compression.